Clinical and dosimetric predictors of radiation pneumonitis in early-stage lung cancer treated with Stereotactic Ablative radiotherapy (SABR) – An analysis of UK's largest cohort of lung SABR patients. (March 2021) - Saha, Animesh; Beasley, Matthew; Hatton, Nathaniel; Dickinson, Peter; Franks, Kevin; Clarke, Katy; Jain, Pooja; Teo, Mark; Murray, Patrick; Lilley, John
Highlights: SABR treatment resulted in very low rate of grade 3 pneumonitis (0.5% in our series). Lower lobe tumour location and tumour size larger than 22.5 mm was significantly associated with higher incidence of ≥grade 2 radiation pneumonitis. PTV of >27.15 cc, mean lung dose of >3.7 Gy, V20 of >4.6% and V12.5 of >9.5% were significantly associated with higher incidence of symptomatic radiation pneumonitis. Abstract: Background: Stereotactic Ablative Radiotherapy (SABR) is the standard treatment for early-stage medically inoperable lung cancer. Predictors of radiation pneumonitis (RP) in patients treated with SABR are poorly defined. In this study, we investigate clinical and dosimetric parameters, which can predict symptomatic RP in early-stage lung cancer patients treated with SABR. Materials and methods: Patients treated with lung SABR between May 2009 and August 2018, in a single United Kingdom (UK) radiotherapy center were included. The patient's baseline characteristics, treatment details, and toxicity were retrieved from the electronic medical record. Dosimetric data was extracted from Xio and Monaco treatment planning systems. Patients were treated according to the UK SABR consortium guidelines. RP was graded retrospectively using Common Terminology Criteria for Adverse Events (CTCAE) version 4.0, based on available clinical and imaging information. Univariate and multivariate binary logistic regression was performed to determine predictive factors for grade ≥ 2 radiation pneumonitis, using Statistical Package for the Social Sciences (SPSS) statistics version 21 software. The goodness of fit was assessed using the Hosmer and Lemeshow test. The optimal diagnostic threshold was tested using the Receiver operating characteristics (ROC) curve. The chi-square test was carried out to test the different risk factors against the likelihood of developing grade ≥ 2 pneumonitis. Results: A total of 1266 patients included in the analysis. The median age of patients was 75 years. Six hundred sixty-six patients (52.6%) were female. Median follow up was 56 months. Sixty-five percent of patients received 55 Gy in 5 fractions. Forty-three percent of patients had Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 2 and 16.2% had PS of 3. The Median Charlson comorbidity index was 6 (range 2–11). Median Standardized Uptake Value (SUV) max of the tumor was 6.5. Four hundred two patients (31.8%) had confirmed histological diagnosis; other patients were treated based on a radiological diagnosis. The median tumor size was 20 mm (range 4 mm–63 mm). Median Planning Target Volume (PTV) was 30.3 cc. Median values of R100, R50, and D2cm were 1.1, 5.6, 32.8 Gy. The median value of mean lung dose, V20, and V12.5 were 3.9 Gy, 5 %and 9.3% respectively. Eighty-five (6.7%) patients developed symptomatic RP (grade ≥ 2) with only 5(0.4%) developing grade 3 RP. Five percent of patients developed rib fractures but only 28% of these were symptomatic. On univariate analysis lower lobe tumor location, larger tumor size, PTV, mean lung dose, lung V20Gy, and V12.5 Gy were significantly associated with grade ≥ 2 RP. On multivariate analysis, only mean lung dose was associated with grade ≥ 2 pneumonitis. ROC curve analysis showed optimal diagnostic threshold for tumour size, PTV, mean lung dose, V20 and V12.5; are 22.5 mm ((Area Under Curve (AUC)-0.565)), 27.15 cc (AUC-0.58), 3.7 Gy (AUC-0.633), 4.6% (AUC-0.597), 9.5% (AUC-0.616). The incidence of ≥grade 2 RP was significantly high for values higher than the ROC threshold. Conclusion: SABR treatment resulted in a very low rate of grade 3 pneumonitis. Lower lobe tumor location, larger tumor size, PTV, mean lung dose, V20, and V12.5 were found to be significant predictors of symptomatic radiation pneumonitis.